2021
DOI: 10.3390/su13084346
|View full text |Cite
|
Sign up to set email alerts
|

Rasch Model for Assessing Propensity to Entomophagy

Abstract: The Food and Agriculture Organization of the United Nations supports the production of edible insects as a promising and sustainable source of nutrients to meet the increasing demand for animal-derived products by the growing world population. Even if insects are part of the diet of more than two billion people worldwide, the practice of eating insects (entomophagy) raises challenging questions for Western countries where this is not a habit. The research applied the Rasch models and showed that, in the case o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 70 publications
0
5
0
Order By: Relevance
“…The separation for item and person for the STEM application instrument in the Indonesian context were 4.67 and 3.81, respectively. The great internal consistency of the instrument was demonstrated by the outstanding outputs of reliability and separation, implying that the instrument can effectively divide items and persons into some categories (Iseppi et al, 2021). Again, in this study, some items revealed high ZSTD scores, indicating a significant misfit, which was one type of measure other than MNSQ, point measure correlation, and separation.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…The separation for item and person for the STEM application instrument in the Indonesian context were 4.67 and 3.81, respectively. The great internal consistency of the instrument was demonstrated by the outstanding outputs of reliability and separation, implying that the instrument can effectively divide items and persons into some categories (Iseppi et al, 2021). Again, in this study, some items revealed high ZSTD scores, indicating a significant misfit, which was one type of measure other than MNSQ, point measure correlation, and separation.…”
Section: Discussionmentioning
confidence: 55%
“…The separation for item (4.67) and person (3.81) for the STEM application instrument in the Indonesian context was good. The excellent results of reliability and separation indicate great internal consistencies of the STEM application instrument (Iseppi et al, 2021).…”
Section: Instrument Validity and Reliabilitymentioning
confidence: 88%
“…On the other hand, previous experience with insects tasting or familiarity with the idea of introducing insects as food were found to increase the willingness to try them [56,71,87,88,94,[100][101][102][103] or to positively affect the hedonic evaluation of insect-based products [74,77]. Familiarity was not an important factor in influencing younger consumers' choice of insectbased food, denoting a major openness [80] and curiosity to novel foods [72,77,104].…”
Section: Insectsmentioning
confidence: 90%
“…Separation for item and person for the mathematical modelling attitude scale in the Malaysian context were 4.67 and 3.81 respectively. The excellent results of reliability and separation showed that the instrument can separate item and person to some groups very well and show high internal consistencies of the instrument (Iseppi et al, 2021).…”
Section: Reliability and Separation Of Instrumentmentioning
confidence: 95%